A study on English-Vietnamese translation of the uniform customs and practice for documentary credits = Nghiên cứu về dịch Anh-Việt của những quy tắc và thực hành thống nhất về tín dụng chứng từ - Phùng, Ngọc Tân (2021)
This research aims at detecting and analyzing the translation methods and translation procedures applied to render the English version of Uniform of Customs and Practice for Documentary Credits into Vietnamese. The research is carried out to answer the research questions which are “what methods and procedures are the most common and the most effective?” and “what are the ways to improve the general quality of the translation?” Observation instrument is implemented to collect the data from the text. Then a number of method and procedure examples are carefully examined and interpreted on the basis of the rudimentary background knowledge in the Literature review section. Results show that there are six procedures (transference, naturalization, through translation, functional translation, transposition and modulation) and two methods (literal and communicative) that were used to translate UCP. Amongst them, through translation were used as the most frequent procedure and literal were used as the most frequent method.